PXR and 4β-Hydroxycholesterol Axis and the Components of Metabolic Syndrome - Janne Hukkanen; Jukka Hakkola (Cells, 2020)
Pregnane X receptor (PXR) activation has been found to regulate glucose and lipid metabolism and affect obesity in response to high-fat diets. PXR also modulates vascular tone. In fact, PXR appears to regulate multiple components of metabolic syndrome. In most cases, the effect of PXR action is harmful to metabolic health, and PXR can be hypothesized to play an important role in metabolic disruption elicited by exposure to endocrine-disrupting chemicals. The majority of the data on the effects of PXR activation on metabolic health come from animal and cell culture experiments. However, randomized, placebo-controlled, human trials indicate that the treatment with PXR ligands impairs glucose tolerance and increases 24-h blood pressure and heart rate. In addition, plasma 4β-hydroxycholesterol (4βHC), formed under the control of PXR in the liver, is associated with lower blood pressure in healthy volunteers. Furthermore, 4βHC regulates cholesterol transporters in peripheral tissues and may activate the beneficial reverse HDL cholesterol transport. In this review, we discuss the current knowledge on the role of PXR and the PXR–4βHC axis in the regulation of components of metabolic syndrome.